EFFECT OF SUGARCANE BY-PRODUCT BASED COMPLETE RATIONS ON GROWTH AND CARCASS CHARACTERISTICS IN BUFFALO BULL CALVES (Indian Journal of Animal Production and Management, 2015)
Six rations comprising of five complete rations and one conventional ration (containing chopped hybrid Napier and concentrate mixture) were formulated by using sugarcane by products and other crop residues and balanced concentrate mixture in the mash form. These rations were compared by feeding to 24 Murrah buffalo bull calves for a period of 167 days using Randomized Block Design to study the effect of processing of complete diet on growth, nutrient utilization and carcass characteristics. Highest ADG (610.0g.) recorded in buffalo bull calves fed on complete ration-II (Sugarcane tops, maize stover and balanced concentrate mixture) when compared among the complete rations and control. The cost of control ration per kg live wt.gain was Rs.41.14.The cost of complete ration per kg live weight gain was higher in control than complete rations though insignificantly different. The cost of complete ration per kg live weight gain was reduced by Rs.3.11, 8.69, 8.60, 10.92 and 8.10 for complete rations-I, II, III, IV and VI, respectively, when compared to control diet. The dressing percentage on live weight was significantly (P
Keywords: Sugarcane by-products; complete ration; growth; meat production; carcass characteristics; Murrah buffaloes bull calves